3D GRAPHICS AND VIRTUAL REALITY TECHNOLOGIES IN FINE ARTS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the application of 3D graphics and virtual reality (VR) technologies in contemporary fine arts. It examines how these technologies are reshaping artistic practice, offering new modes of visual expression, audience interaction, and narrative construction. The study highlights the conceptual and aesthetic potentials of 3D and VR in creating immersive experiences, expanding the spatial and sensory dimensions of art. Furthermore, the article analyzes how these technologies influence art education, interdisciplinary collaboration, and the evolution of visual culture in the digital era.